Lack of Tenderness: The Main Culprit for the Relationship between Husband and Wife in Lady Chatterley’s Lover - Kifayatullah (University of Chitral Journal of Linguistics and Literature, 2020)
This article presents the case of Chatterley and Clifford, the two main characters in Lady Chatterley’s Lover, to consider tenderness a basic working emotion to shape human relationship. The lack of tenderness causes emotional as well as physical distance in relation, especially that of male-female’s relation. The first part of the article reviews tenderness. The second part reviews how tenderness and lack of tenderness affects male-female relationship in the selected novel, Lady Chatterley’s Lover. On the basis of a careful analysis of Lady Chatterley’s Lover, the present writer tries to prove that the lack of tenderness is the main culprit for the broken relationship between husband and wife: a major one of the relations between man and woman in human society and mutual tenderness elicits people awakening to a new way of living in an exterior world that is uncracking after the long winter hibernation. Lawrence, through revelation of Connie’s gradual awakening from tenderness, has made his utmost effort to explore possible solutions to harmonious androgyny between men and women so as to revitalize the distorted human nature caused by the industrial civilization.